Effects of Friction Stir Welding Parameters of Dissimilar Aluminum Alloys on Residual Stress and Microhardness - Adirek Baisukhan (2020)
© Published under licence by IOP Publishing Ltd. The aim of this research is to use a full factorial design to determine the significant factors of friction stir welding (FSW) process of dissimilar AA6061-T6 and AA7075-T651 aluminum alloys, on the surface residual stress and microhardness. There are a total of three factors studied: rotation speed, welding speed and workpiece layout. The results showed that the factors that have a statistically significant effect on residual stress occurring are welding speed, workpiece layout and interaction between rotation speed and welding speed. The appropriate parameters for FSW process of dissimilar aluminum alloys are rotation speed of 1400 rpm, welding speed of 50 mm/min and the layout of the workpiece by advancing side (AS) uses AA6061-T6 sheet, while retreating side (RS) uses AA7075-T651 sheet, which will result in the surface residual stress of -34.33 MPa. This compressive residual stress will be beneficial to the welded joint for retard the occurrence of cracks caused by fatigue. The hardness of all workpieces have similar tendency, thermo-mechanically affected zone (TMAZ) area in both AS and RS gave the least hardness, which found that the AA6061-T6 and AA7075-T651 sheets had a hardness of approximately 55HV and 110HV respectively.